Health, performance, and greenhouse gas emissions intensity in U.S. feedlot cattle - McAtee, Taylor B. (My University, 2026)
Sustainability in beef production is increasingly evaluated using greenhouse gas emissions metrics, yet environmental performance in feedlot systems is inherently linked to biological efficiency and animal health. As sustainability targets expand across the beef supply chain, there is a need for production-relevant, outcomes-based approaches that integrate routinely collected health and performance data into emissions assessments. The primary objectives of this dissertation were to: evaluate the effects of production and health metrics on greenhouse gas emissions intensity (EI) in U.S. feedlot systems; assess the environmental and economic impacts of a feed additive approved for emissions reduction; quantify associations among disease burden, mortality, growth performance, and EI using commercial-scale observational data; evaluate the effectiveness of alternative treatment strategies for bovine respiratory disease (BRD); and synthesize these findings into a systems-based framework linking animal health, production efficiency, and sustainability outcomes. A large-pen commercial feedlot trial compared cattle fed lubabegron (Experior), the first U.S. Food and Drug Administration–approved feed additive for reducing gas emissions from cattle, with cattle fed ractopamine hydrochloride (Optaflexx). Cattle fed lubabegron exhibited improved growth performance and feed efficiency, reduced dry matter intake, and heavier carcass weights relative to comparator cattle. These performance differences translated to a 6.2% reduction in estimated carbon dioxide equivalent emissions per unit of carcass weight and greater estimated net returns per animal shipped. Complementary observational research using commercial feedlot data demonstrated that higher average daily gain and improved gain-to-feed ratio were consistently associated with lower lifetime EI across diverse production conditions. However, effect magnitudes varied by sex and season, highlighting biological and management heterogeneity inherent to commercial systems. Associations between animal health and EI also were evaluated. Increased disease burden and mortality were consistently associated with higher EI, reflecting extended days on feed, impaired feed efficiency, and the loss of productive output from invested resources. Reducing mortality from 5% to 0% was estimated to lower lifetime EI by approximately 6%, illustrating the environmental consequences of lost production. A randomized clinical trial comparing tulathromycin, tulathromycin plus ketoprofen, and tildipirosin for first treatment of naturally occurring BRD in medium-risk feedlot cattle demonstrated no significant differences in morbidity, retreatment risk, or mortality across treatment groups. These findings indicate that sustainability impacts of health interventions are context-dependent and contingent upon measurable effects on downstream performance outcomes. Across study designs, production efficiency emerged as a central driver of EI. Cattle that grow more rapidly and convert feed more efficiently require fewer biological and material inputs per unit of beef produced, thereby reducing EI. Conversely, health challenges that impair growth or result in mortality increase EI by elevating inputs relative to productive output. Importantly, this work distinguishes between total emissions and EI, demonstrating that reductions in total emissions may coincide with increased mortality or reduced productivity if evaluated without appropriate functional units. This dissertation integrates epidemiological methods, commercial production data, and emissions modeling to provide a pragmatic framework for evaluating sustainability in feedlot systems. The findings demonstrate that animal health, production efficiency, and environmental performance are tightly linked components of a single biological system. Improvements in health and growth efficiency align economic, environmental, and animal welfare objectives within commercially relevant production systems. Collectively, this work supports the conclusion that healthier, more efficient cattle are inherently more sustainable, and that meaningful progress toward beef sustainability goals will depend on optimizing core health and production management practices rather than relying solely on stand-alone environmental interventions.
Keywords: Beef cattle; Feedlot; Greenhouse gas emissions; Sustainability; Animal health; Production efficiency